(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Airport Management System: The Airport Customer Guest Management Relationship, Ticketing and Payment, Baggage Control and Information, Flight Schedule and Rate Management, and Messenger Module are all aided by the Core Transaction 1 system. Create well-organized software to handle customers’ data and the reservation procedure. Customers can make reservations or bookings online using the Airport Management System Core Transaction 1. Throughout this project, the project team employed the Agile Methodology. In order to comprehend the Airport Management process, the project team gathers relevant project studies before starting the project. The project team divides planning into distinct sprints and generates backlogs. Every day during their stand-up meeting, the project team reviews how the project is doing. In order to evaluate the sprints developed to enhance the system as a whole, the project team will lastly do a sprint evaluation and retrospective for each sprint. It so resolves the issue and difficulty with the Airport Management System. The Airport Skystream Enterprises system, the newly improved version of Core Transaction 1, is designed to be user-friendly and easy for users to become associated with and comprehend. Furthermore, we improved the system with some new features like online booking, searchable flights to their destination, adaptable payment options, and departure and arrival status tracking. The functionality and operations of Airport Management will be enhanced by this project. Core transaction 1 secures sensitive information within the system. It keeps track of client records, personnel information, and prospective customers of Skystream Enterprises, all of which are crucial to preserve. Because of this, we require the impenetrable and safe security measures that we have put in place, such as data privacy, strong passwords, and system session timeouts, to deter hackers. In addition, the system features a database file that holds the data and backs up the information in case the data gets collapsed.